Revitalization of Education in Indonesia to Educational Institutional Organizations in Southeast Asian Countries - Muslim Muslim (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2022)
The Southeast Asian region consists of countries with diverse religious adherents. To examine the Organization of Educational Institutions throughout Southeast Asia, samples were taken from countries with a majority Muslim population and countries with a minority Muslim religion. Countries with Muslim majority adherents are Indonesia, Malaysia, and Brunei Darussalam, while countries with minority Muslims are Thailand, Singapore, and the Philippines. The development of Islamic educational institutions in Indonesia, among others, is marked by the gradual emergence of various educational institutions, ranging from simple ones to stages that are considered modern. Islamic educational institutions have played their functions and roles to the demands of society and their times. The development of these educational institutions has attracted the attention of experts both from within and outside the country to conduct comprehensive scientific studies. Now many research works of experts inform about the growth and development of these Islamic educational institutions. The aim is not only to enrich the treasures of knowledge with Islamic nuances as well as referecomparemparison material for managers of Islamic education in the following periods.